Tissue Engineered Vascular Graft Recipient Interleukin 10 Status Is Critical for Preventing Thrombosis. Issue 24 (19th October 2020) - Mirhaidari, Gabriel J. M.; Barker, Jenny C.; Zbinden, Jacob C.; Santantonio, Brevan M.; Chang, Yu‐Chun; Best, Cameron A.; Reinhardt, James W.; Blum, Kevin M.; Yi, Tai; Breuer, Christopher K.
Abstract: Tissue engineered vascular grafts (TEVGs) are a promising technology, but are hindered by occlusion. Seeding with bone‐marrow derived mononuclear cells (BM‐MNCs) mitigates occlusion, yet the precise mechanism remains unclear. Seeded cells disappear quickly and potentially mediate an anti‐inflammatory effect through paracrine signaling. Here, a series of reciprocal genetic TEVG implantations plus recombinant protein treatment is reported to investigate what role interleukin‐10, an anti‐inflammatory cytokine, plays from both host and seeded cells. TEVGs seeded with BM‐MNCs from wild‐type and IL‐10 KO mice, plus unseeded grafts, are implanted into wild‐type and IL‐10 KO mice. Wild‐type mice with unseeded grafts also receive recombinant IL‐10. Serial ultrasound evaluates occlusion and TEVGs are harvested at 14 d for immunohistochemical analysis. TEVGs in IL‐10 KO mice have significantly higher occlusion incidence compared to wild‐type mice attributed to acute (<3 d) thrombosis. Cell seeding rescues TEVGs in IL‐10 KO mice comparable to wild‐type patency. IL‐10 from the host and seeded cells do not significantly influence graft inflammation and macrophage phenotype, yet IL‐10 treatment shows interesting biologic effects including decreasing cell proliferation and increasing M2 macrophage polarization. IL‐10 from the host is critical for preventing TEVG thrombosis and seeded BM‐MNCs exert a significant anti‐thrombotic effect in IL‐10 KO mice. Abstract : Seeding tissue engineered vascular grafts (TEVGs) with bone‐marrow derived mononuclear cells improves patency potentially through an interleukin 10 (IL10) mediated paracrine mechanism. In a series of reciprocal genetic experiments, unseeded, wild‐type seeded, and IL‐10 KO seeded TEVGs are implanted into wild‐type recipient and IL‐10 KO recipient mice to determine the role of secreted/host IL‐10 on TEVG patency and neotissue development.